2013
DOI: 10.1002/pam.21739
|View full text |Cite
|
Sign up to set email alerts
|

Tax Code Knowledge and Behavioral Responses Among EITC Recipients: Policy Insights from Qualitative Data

Abstract: We build on the robust quantitative literature on behavioral responses to the Earned Income Tax Credit (EITC) by using in‐depth qualitative interviews with 115 EITC recipients to examine how they understand and respond to its incentive structures regarding earnings, marriage, and childbearing. We find that respondents consider their tax refund as a whole, without differentiating the portion from the EITC; as a result, they cannot predict how their EITC refund would change if they altered their labor supply or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Qualitative evidence on the EITC indicates that recipients tend to view and spend the lump sum differently than they do their usual income. 42,43 They also use the lump sum to make larger purchases and invest in durable goods. 44 How this translates into health improvements in the longer term should be the subject of future research.…”
Section: Exhibitmentioning
confidence: 99%
“…Qualitative evidence on the EITC indicates that recipients tend to view and spend the lump sum differently than they do their usual income. 42,43 They also use the lump sum to make larger purchases and invest in durable goods. 44 How this translates into health improvements in the longer term should be the subject of future research.…”
Section: Exhibitmentioning
confidence: 99%
“…Among current policies, the Earned Income Tax Credit (EITC) often serves as a de facto emergency savings vehicle for poor families. Families use the credit, which is delivered as a once yearly lump‐sum, for a variety of purposes including placing a portion in savings (Edin, Tach, & Halpern‐Meekin, ; Mendenhall et al, ; Romich & Weisner, ). Examinations of bank records from EITC recipients who participated in a savings incentive program showed that many who put funds into savings spent the funds down within 4 months (Beverly, Tescher, Romich, & Marzahl, ).…”
Section: How Policies and Programs Could Reduce Or Moderate Economic mentioning
confidence: 99%
“…Substantial research has explored the work incentive and other behavioral effects of the EITC. See Dickert‐Conlin, Houser, and Scholz (); Hotz and Scholz (, ); Hoynes and Eissa (); Hoynes (); Blank, Danziger, and Schoeni (); Edin, Tach, and Halpern‐Meekin (); and Neumark ().…”
mentioning
confidence: 99%